Madelung’s disease: a case report in an Asian patient - Mohd. Sa’im, Nur Fiza Izrin; Abdul Hadi, Azwanis (UniKL, 2023)
A middle-aged man presented with a slow-growing circumscribed mass over both upper arms associated with muscle soreness and lethargy. He has a history of chronic alcohol consumption and imaging studies revealed subcutaneous fat tissue hypertrophy. The characteristics of his disease fit a rare symmetrical lipodystrophy disorder known as Madelung’s disease (MD). This is a report detailing the description of the case.